2008
DOI: 10.1371/journal.ppat.1000213
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Chelates Cations and Induces Antibiotic Resistance in Pseudomonas aeruginosa Biofilms

Abstract: Biofilms are surface-adhered bacterial communities encased in an extracellular matrix composed of DNA, bacterial polysaccharides and proteins, which are up to 1000-fold more antibiotic resistant than planktonic cultures. To date, extracellular DNA has been shown to function as a structural support to maintain Pseudomonas aeruginosa biofilm architecture. Here we show that DNA is a multifaceted component of P. aeruginosa biofilms. At physiologically relevant concentrations, extracellular DNA has antimicrobial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
546
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(584 citation statements)
references
References 79 publications
13
546
2
5
Order By: Relevance
“…pilA transcription in various P. aeruginosa strains was measured in 96-well plate liquid cultures similar to the method described in ref. 55. Briefly, bacterial strains carrying the pMS402+ ppilA plasmid were grown for 16 h at 37°C in 5 mL LB-Kan, 150 μg/mL Cultures were then diluted 1:20 in fresh media and grown to a standardized OD 600 = 0.15, and the OD 600 and relative luminescence of each culture were measured at 15-min intervals using a Synergy 4 microtiter plate reader (BioTek) for 5h.…”
Section: Methodsmentioning
confidence: 99%
“…pilA transcription in various P. aeruginosa strains was measured in 96-well plate liquid cultures similar to the method described in ref. 55. Briefly, bacterial strains carrying the pMS402+ ppilA plasmid were grown for 16 h at 37°C in 5 mL LB-Kan, 150 μg/mL Cultures were then diluted 1:20 in fresh media and grown to a standardized OD 600 = 0.15, and the OD 600 and relative luminescence of each culture were measured at 15-min intervals using a Synergy 4 microtiter plate reader (BioTek) for 5h.…”
Section: Methodsmentioning
confidence: 99%
“…The cause of such increased tolerances seen in biofilms has been investigated in a number of different studies, focusing on the extracellular matrix, the involvement of quorum sensing (QS), and the physiological factors observed within the biofilm [19,[26][27][28][29]. The extracellular matrix itself has been shown to obstruct the diffusion of some antimicrobial agents through both chemical and physiological means [27,30,31]. The matrix however is not selective against antimicrobial agents, and therefore the diffusion of many substances, such as oxygen, metabolites and waste products, can also be altered.…”
Section: The Role Of Biofilms During Chronic Infectionmentioning
confidence: 99%
“…[2][3][4][5][6] In E. coli cells, FQN can be extruded from the outer or inner membrane through the action of various efflux pumps. Previous studies have reported that acrAB, mdfA and norE are involved in FQN resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of FQN resistance in various bacteria include biofilm formation, overexpression of multidrug efflux pump related genes and chromosomal mutations of DNA gyrase and topoisomerase IV. [2][3][4][5][6] Phage shock protein (psp) response and pilus operons play an important role in acquiring pathogenesis of UTI and biofilm formation in E. coli. [7][8][9] Many investigators are making every effort to overcome FQN resistance by investigating novel mechanisms.…”
Section: Introductionmentioning
confidence: 99%